2014
DOI: 10.7220/2335-2027.5.8
|View full text |Cite
|
Sign up to set email alerts
|

Wikis as a Tool for Collaborative Language Learning: Implications for Literacy, Language Education and Multilingualism

Abstract: Summary. This study presents a review of the literature concerning the use of wikis as a tool for collaborative learning in the second language acquisition and foreign language learning process, as research on the use of wikis is relatively new. The study first introduces the theoretical background behind the use of wikis in the mentioned processes. Then, it reviews the studies concerning wikis as a tool for collaborative language learning. The study concludes that the use of wikis improves basic language skil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 59 publications
3
9
0
Order By: Relevance
“…If we look at Axis B results in table 2, it can be assumed that wikis are an effective tool to enhance students' motivation to learn vocabulary and English in general. Same findings can be read in many studies such as Arnold et al (2012), Awada and Diab (2018), Aydin (2015), Isa (2012), Mohammed (2013).…”
Section: What Can Wiki Do To Motivate Students To Learn English Vocabsupporting
confidence: 60%
“…If we look at Axis B results in table 2, it can be assumed that wikis are an effective tool to enhance students' motivation to learn vocabulary and English in general. Same findings can be read in many studies such as Arnold et al (2012), Awada and Diab (2018), Aydin (2015), Isa (2012), Mohammed (2013).…”
Section: What Can Wiki Do To Motivate Students To Learn English Vocabsupporting
confidence: 60%
“…The findings of this study shed light on the effectiveness of wiki-based activities and forums in the development of the second-language students' written skills [28,29], and their impact on the collaborative autonomy [2,3,4] in a blended learning course. The learning outputs and the learners' improvements in their level of the grammatical and discourse competences, in their confidence in second language (L2) as well as in their vocabulary and knowledge of the English culture are in line with the positive results pointed out previously.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Other studies were more concerned with analyzing students" writing subskills and perception towards writing. For instance, Tsoi (2010), Ciftci and Kocoglu (2012) and Aydin (2014) reported that incorporating Web 2.0 collaborative activities, including blogs and wikis, improved students" writing content, collaboration and task management. This is attributed to the shared knowledge production compared to individualized models of writing.…”
Section: Collaborative Writingmentioning
confidence: 99%